Light physical activity and vitamin D improve sperm quality of male Rattus norvegicus exposed to cigarette smoke - Meriana Barreto Amaral; Bagus Komang Satriyasa; I Wayan Putu Sutirta Yasa; I Made Sudarmaja; I Made Jawi; Ida Bagus Putra Manuaba; Ni Made Linawati; I Gusti Ayu Widiyanti (Universitas Udayana dan Diaspora Taipei Medical University, 2025)
Background: Male infertility is a significant global health issue, with rising prevalence linked to environmental factors such as secondhand smoke, which impairs sperm quality. This study aimed to examine how light physical activity and vitamin D supplementation improved sperm quality in rats exposed to cigarette smoke. Methods: This study used a randomized experimental design with 38 rats, divided into two groups. The control group was exposed to cigarette smoke and received vitamin D at 18 IU/kg body weight (BW) daily. The treatment group was exposed to cigarette smoke, received the same vitamin D dose, and underwent light physical activity. The 35-day research period involved the analysis of evaluated parameters. Differences between these parameters were assessed using an independent t-test, with statistical significance set at a P-value < 0.05. Results: Compared to the control group (p-values< 0.001), the treatment group, receiving light physical activity and vitamin D supplementation, exhibited significantly lower malondialdehyde (MDA) levels (0.96 ± 0.14 nmol/mL), higher vitamin D receptor expression (2.44 ± 0.58 cells/HPF), and increased testosterone levels (4.33 ± 0.76 ng/dL). Sperm quality was also significantly improved in the treatment group, showing higher sperm count (2.24 ± 0.81 × 10⁶/mL), motility (4.20 ± 0.23%), viability (3.07 ± 0.39%), and normal morphology (5.34 ± 0.17%) (p-values< 0.001). Conclusion: Light physical activity and vitamin D supplementation improved sperm quality in cigarette smoke-exposed male rats, correlating with reduced MDA and elevated vitamin D receptor expression and testosterone. Further clinical trials are warranted to explore human applications.